2010
DOI: 10.1007/s10048-010-0268-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea enhances SMN2 gene expression through nitric oxide release

Abstract: Small molecules that increase full-length survivor motor neuron (SMN) gene transcript are promising therapeutic candidates for spinal muscular atrophy (SMA). Hydroxyurea (HU) has recently been shown to increase full-length SMN transcript in cultured lymphocytes from patients with SMA. We investigate the mechanism by which HU enhances full-length SMN2 gene expression in SMA lymphocytes. Nitric oxide (NO) is a major intracellular metabolite of HU. We test whether NO donors can themselves enhance full-length SMN2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…It has recently been suggested that HU enhances SMN2 expression in lymphoblasts through the release of nitric oxide but its mechanism of action on SMN2 genes is as yet unknown. 37 In the present study, the three compounds tended to show a different intra-patient response depending on the tissues under investigation. This can be partially explained by the fact that fibroblasts are primary cultures that grow as monolayers, whereas lymphoblasts are EBV-immortalized cells that grow in suspension.…”
Section: Discussionmentioning
confidence: 51%
“…It has recently been suggested that HU enhances SMN2 expression in lymphoblasts through the release of nitric oxide but its mechanism of action on SMN2 genes is as yet unknown. 37 In the present study, the three compounds tended to show a different intra-patient response depending on the tissues under investigation. This can be partially explained by the fact that fibroblasts are primary cultures that grow as monolayers, whereas lymphoblasts are EBV-immortalized cells that grow in suspension.…”
Section: Discussionmentioning
confidence: 51%
“…[80][81][82] A small pilot study of hydroxyurea at 3 different doses for 8 weeks in 33 types II and III patients, however, showed no statistically significant benefit. 81 A randomized, double-blind, placebocontrolled trial failed to show any improvement over an 18-month period.…”
Section: Agents That Up-regulate Survival Of Motor Neuron 2 Gene Exprmentioning
confidence: 94%
“…The drug hydroxyurea, approved by the United States Food and Drug Administration, was identified in the course of drug screens, using cell lines from patients with spinal muscular atrophy, to increase the amount of full-length SMN transcript and protein in vitro [101][102][103]. However, a small pilot study of hydroxyurea at three different doses for 8 weeks in 33 patients with types II and III demonstrated no statistically significant benefit [102].…”
Section: Clinical Trials In Spinal Muscular Atrophy: Therapeuticsmentioning
confidence: 97%